Self-efficacy development in school principal enhancement programs - Albor, R. G. Z.; Quimbo, M. T.; Dizon, J. T. (2003)
This mixed methods study aimed to describe the elements in Principal Enhancement Program (PEP) of selected principals in Southern Tagalog municipality in the Philippines; identify specific elements in PEP which contributed to the self-efficacy of principals; identified development; and recommend ways on how PEP might more purposefully design experiences during the PEP that contribute to self- efficacy development. Principals with highly rated PEP and self-efficacy were chosen for qualitative interviews. PEP were received to be most effective in encouraging collegial relationships and self-reflection practices promoting policy/procedure knowledge, and practiced supervision. The spearman correlation analysis showed that instruction, relevance of coursework to practice and field experience elements were significantly associated with self-efficacy. Interview transcript revealed that instructional experiences and leadership experiences before principalship are crucial to self-efficacy development. To purposely create efficacy-building experiences, PEP should design experiences that cause students to work with other people; develop extensive field experiences; and make leadership experiences a prerequisite to principalship.
Keywords: School principals; Self-efficacy